2008
DOI: 10.1111/j.1365-2052.2008.01755.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of an insulin‐like growth factor 1 gene microsatellite with phenotypic variation and estimated breeding values of growth traits in Canchim cattle

Abstract: A population of 1398 Canchim (CA) cattle was genotyped to assess the association of an insulin-like growth factor 1 (IGF1) gene microsatellite with phenotypic variation and estimated breeding values of pre-weaning, weaning and post-weaning growth traits. After an initial analysis, the IGF1 genotype only had a significant effect (P < 0.05) on birth weight (BW) and weaning weight adjusted to 240 days (WW240). For these two traits, direct and maternal breeding values were estimated using the restricted maximum li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 17 publications
3
38
3
2
Order By: Relevance
“…According to Islam et al (2009), several studies have identified a quantitative trait locus (QTL) associated with carcass traits in the vicinity of IGF1 in beef cattle. Several studies have associated polymorphisms in IGF1 with growth traits in beef cattle as well (Pereira et al, 2005;Andrade et al, 2008). Islam et al (2009) have associated an SNP in the promoter region of IGF1, the same region in which the microsatellite used in this study resides with fat deposition and other carcass traits in crossbred Angus and Charolais beef cattle.…”
Section: Resultsmentioning
confidence: 99%
“…According to Islam et al (2009), several studies have identified a quantitative trait locus (QTL) associated with carcass traits in the vicinity of IGF1 in beef cattle. Several studies have associated polymorphisms in IGF1 with growth traits in beef cattle as well (Pereira et al, 2005;Andrade et al, 2008). Islam et al (2009) have associated an SNP in the promoter region of IGF1, the same region in which the microsatellite used in this study resides with fat deposition and other carcass traits in crossbred Angus and Charolais beef cattle.…”
Section: Resultsmentioning
confidence: 99%
“…In goats, the microsatellite had effects on birth weight . In cattle, this microsatellite was associated with birth weight and weaning weight in the early growth phase (Andrade et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Growth and meat quality traits are economically important factors of beef cattle and are controlled by multiple genes (Andrade et al, 2008;Liu et al, 2012). Association studies cannot determine whether gene markers are responsible for variations in a trait, or whether such variation is influenced by closely linked loci.…”
Section: Introductionmentioning
confidence: 99%